Why vernacular language planning matters for preserving Acehnese languages? - Syahputera, Iskandar; Ginting, Siti Aisah; Saragih, Amrin; Sibarani, Berlin; Ginting, Immanuel Prasetya; Lubis, Fauziah Khairani; Natsir, Muhammad; Indah Pane, Isli Iriani (Universitas Islam Negeri Banda Aceh, 2024)
Language planning policy is essential for language preservation, yet research rarely addresses vernacular or local languages specifically. This study examines how vernacular language planning policies can contribute to the preservation and revitalization of local languages, focusing on the case of Aceh, a province in Indonesia with a rich variety of local languages requiring preservation efforts. The study’s primary goal is to identify an effective framework for vernacular language planning in Aceh that can serve as a practical reference for language policymakers, planners, and researchers in Indonesia and beyond. Utilizing a systematic review method, this research analyzes literature on language vitality, endangerment, revitalization, and planning policy. Key findings reveal a newly developed vernacular language planning framework tailored to the current vitality status of Acehnese languages, offering a suitable model for their preservation and revitalization. This framework has the potential to serve as a foundational tool for efforts to sustain and revive Acehnese and other vernacular languages more broadly.